THE COMMITMENT BEHAVIOR OF FISHERS TOWARDS THE DEVELOPMENT OF THEIR COMMUNITY A Case Study in Demak Central Java – Indonesia - Indah Susilowati (JOURNAL OF COASTAL DEVELOPMENT, 2003)
The commitment of fishers towards their community development is investigated in this study. Several statistical tools such as discriminant analysis, cross-tabulation and compare means with independent t-test have been employed to analyze the data which were collected from 56 samples in the study area of Wedung and Moro Demak, Demak Regency. The results showed that the commitment behaviour of fishers might be guided by several variables such as Age, Sex, Educ, Exper, Inc, Stay. In order to improve the commitment levels of respondents, thus, magnitude of the observed variables in the model could be explored further. Lastly, the model of fishers’ commitment with discriminant analysis performes fairly good with the right prediction of the original grouped cases is correctly classified for about 62.5%.